PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KARAKTER DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) POKOK BAHASAN PERSAMAAN LINIER SATU VARIABEL DI KELAS VII SEMESTER GANJIL SMP NEGERI 3 BANGSALSARI TAHUN AJARAN 2012/2013 - Pradhana, Dewangga; Hobri, H; Susanto, S (Department of Mathematics Education , University of Jember, 2014)
Abstract. Development of the character-based approach to Contextual Teaching and Learning. Contextual Teaching and Learning is one of learning method that make students learn mathematics by connecting the material to the real life. The material is drawn is a linier equation of one variable in class VII junior hight school of SMPN 3 Bangsalsari. In this development using the development model camps. The charakters are developed responsibility, respect and discipline. The device being developed include the lesson plan, student worksheet, and student book. The data collection method used in this research with question responses, student observation, teacher observation and student achievement test. The result of the validation study validity coefficient lesson plans, student books, student worksheet, respectively 0,818; 0,791; 0,812. Observation of the average activity of teachers in managing the learning of 88.00% and analysis average student activity by 88.89% with Average achievement test mastery of 75.97. From analisis it was found that devices made have valid, practical and effective. Key Words : Lesson plan, student worksheet, student book.